Survival impact of the Australian National Bowel Cancer Screening Programme. Issue 2 (February 2016) - Ananda, S.; Wong, H.; Faragher, I.; Jones, I. T.; Steele, M.; Kosmider, S.; Desai, J.; Tie, J.; Field, K.; Wong, R.; Tran, B.; Bae, S.; et al.
Abstract : Background: The Australian National Bowel Cancer Screening Program (NBCSP) has been offering age‐based faecal occult blood testing since 2006. With the rapid expansion of this programme, the NBCSP will ultimately offer biennial screening to all 50–74 years old by 2020. Participation rates remain low. Previous reports have described an increased proportion of earlier stage cancers in patients with NBCSP‐detected tumours. Methods: Data on consecutive patients enrolled into a prospective, comprehensive, multidisciplinary database at six Victorian hospitals were examined. Clinicopathologic and outcome data were compared for NBCSP and symptomatic presentation patients. Results: We identified 3743 patients that presented with colorectal cancer (CRC) at participating hospitals since May 2006. Of 1930 patients aged between 50 and 70 years, 141 (7.3%) had a NBCSP detected cancer, 1441 (74.7%) presented with symptoms and 266 (13.8%) were diagnosed through screening outside of the NBCSP. Based on the American Society of Anaesthesiology score, the NBCSP patients were fitter. They had an earlier stage of diagnosis and were more likely to be female and less likely to have lymphovascular invasion or to present as an emergency. NBCSP detected patients had a lower rate of recurrence (HR 0.17, P  = 0.0001) and fewer deaths (HR 0.19, P  = 0.005). Conclusions: Patients with NBCSP‐detected CRC have a markedly reduced risk of CRC recurrence and death compared with patients with a symptomatic presentation. The dominant driver of this appears to be earlier stage at diagnosis. Increased promotion of the impact of the NBCSP, including data related to the survival impact, should be undertaken to increase participation rates and achieve further survival gains.